The Role of Teacher's Teaching Style and in Increasing Students' Motivation towards Islamic Religious Education Learning Outcomes - Beni Kurniawan (GoAcademica Research & Publishing, 2022)
The results of the PAI subject scores of students at SD Negeri 03 Petanahan show that the students' level of interest in Islamic religious education (PAI) is still very low. This can be observed from the fact that the students' scores are still below the target that is intended to be accomplished. One of the reasons for this is that there is a lack of interest and drive among the students, as well as a one-way teaching approach in which the instructor is the focal point. Therefore, the purpose of this study is to identify the effect that teacher motivation and teaching style have in improving the learning outcomes of Islamic Religious Education at SD Negeri 03 Petanahan. Specifically, this research will be conducted in Petanahan. Descriptive qualitative research was conducted for the purpose of this study, with a literature review serving as the primary data collection method. The findings demonstrated that the instructor's method of instruction, which included a variety of movement, variations in voice, shifting positions, and a nature of learning that was not only in one direction, was able to increase zeal and interest in Islamic Religious Education topics. This was demonstrated by the fact that the enthusiasm and interest of the students increased. While the motivation of students in this institution is very important, it is also very necessary to cultivate positive habits outside of the regular school day, such as the habit of praying, the habit of welcoming others, and so on.